Cybersecurity Vulnerability Behavior Scale in College During the Covid-19 Pandemic - Hendro Wijayanto; Iwan Ady Prabowo (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
The penetration of Indonesian internet users in first quarter of 2020 has increased by 17 percent compared to 2019. Based on Google Consumer Barometer in 2018, many 79% of Internet users in Indonesia use the internet on a daily basis. During the Covid-19 Pandemic, universities had to do Study From Home and Work From Home. This resulted, use of information technology and computers also increasing. This increase will have an impact on the level of cybercrime vulnerability. The scale of cyber vulnerability is needed to measure level of cybersecurity in universities, especially in data managers. There are five scales, Very Safe, Safe, Vulnerable, Very Vulnerable, and Dangerous. Where the scale is used in negative and positive statements. The measurement results show an average value of 3.3 or a vulnerable scale. Total average value of negative statements is 2.53 or scale close to vulnerability. So it is necessary to socialize the importance of cybersecurity to minimize occurrence of cybercrime.